Employment status and differences in the one-year coverage of physician visits: different needs or unequal access to services? - Kivimäki Mika; Virtanen Pekka; Vahtera Jussi; Koskenvuo Markku (BMC, 2006)
Abstract Background The dichotomy employed vs. unemployed is still a relevant, but rather crude measure of status in current labour markets. Also, studies concerning the association of employment status with health have to specify the type of the employment as well as the characteristics of the unemployment. This study aims to reveal differences and potential inequalities in physician visits among seven groups in the core-periphery structures of the labour markets. Methods A total of 16 000 Finns responded to a postal survey in 2003. Their visits to physicians in public primary health care, occupational health care, private health services, hospital outpatient clinics and dental care services during previous year were measured as indicators of service utilisation. Participants were classified as employees having a permanent or fixed-term and full-time or part-time contract and as those experiencing short-term, prolonged or long-term unemployment. Differences in the one-year coverage of physician visits between these groups of employees were analysed using logistic regression analyses where differences in the need for services were controlled for by including demographics and self-rated health assessments in the models. Results Permanently employed respondents had visited a physician most often, and the need-adjusted regression models showed significantly lower odds ratios for a visit among fixed-term employees (OR 0.65, 95% CI 0.53-0.81) and in particular among the long-term unemployed (OR 0.21, 95% CI 0.14-0.31). A stratified analysis according to health care sector showed the lowest odds ratios in occupational health care and private physicians (ORs between 0.05 and 0.73) and also low odds ratios for dentists (ORs between 0.45 and 0.91), whereas visits to public primary health care were more common among non-permanent employees and the unemployed (ORs between 1.46 and 2.39). Conclusion The use of physician services varies according to labour market status, being relatively low among the non-permanently employed and the unemployed. This underuse is emphasised when clinical need is taken into account. The main reasons for the variance evidently lie in the structures of the Finnish health service system. The result may indicate non-optimal health care of the population on the periphery of the labour market, but it may also reflect the importance of employment status as a context for need and the decision to visit a physician.